2020
DOI: 10.1111/liv.14542
|View full text |Cite
|
Sign up to set email alerts
|

Hepatocyte KLF6 expression affects FXR signalling and the clinical course of primary sclerosing cholangitis

Abstract: Background & Aims Primary sclerosing cholangitis (PSC) is characterized by chronic cholestasis and inflammation, which promotes cirrhosis and an increased risk of cholangiocellular carcinoma (CCA). The transcription factor Krueppel‐like‐factor‐6 (KLF6) is a mediator of liver regeneration, steatosis, and hepatocellular carcinoma (HCC), but no data are yet available on its potential role in cholestasis. Here, we aimed to identify the impact of hepatic KLF6 expression on cholestatic liver injury and PSC and ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 49 publications
(55 reference statements)
0
2
0
Order By: Relevance
“…On the contrary, when FXR is reduced, tumor growth may continue. Therefore, we found that the expression of FXR in tumor cells of hilar cholangiocarcinoma was significantly lower than that in normal tissues 14 . Second, it controls the excretion and reabsorption of bile acids by regulating the target gene of bile salt export pump (BSEP, regulation of bile acid secretion) and sodium taurocholate transporter (NTCP, regulation of bile acid reabsorption), so as to maintain the stability of bile acid concentration 15 , avoid excessive accumulation of bile acids in the bile duct, lead to the occurrence of stones and cholangitis, cause repeated destruction and proliferation of bile duct cells, the emergence of heterogenous cells, and promote the further development of tumors.…”
Section: Discussionmentioning
confidence: 77%
“…On the contrary, when FXR is reduced, tumor growth may continue. Therefore, we found that the expression of FXR in tumor cells of hilar cholangiocarcinoma was significantly lower than that in normal tissues 14 . Second, it controls the excretion and reabsorption of bile acids by regulating the target gene of bile salt export pump (BSEP, regulation of bile acid secretion) and sodium taurocholate transporter (NTCP, regulation of bile acid reabsorption), so as to maintain the stability of bile acid concentration 15 , avoid excessive accumulation of bile acids in the bile duct, lead to the occurrence of stones and cholangitis, cause repeated destruction and proliferation of bile duct cells, the emergence of heterogenous cells, and promote the further development of tumors.…”
Section: Discussionmentioning
confidence: 77%
“…A previous study demonstrated that higher hepatic KLF6 expression is associated with a better prognosis in primary sclerosing cholangitis, which is a chronic liver disease, and KLF6 regulates FXR signaling by binding to FXREs ( 42 ). KLF6 can also affect lipid metabolism and activate the mTOR signaling pathway, thereby promoting the progression of renal clear cell carcinoma ( 43 ).…”
Section: Discussionmentioning
confidence: 99%